EFFECT OF OBSTRUCTIVE SLEEP APNEA (OSA) RISK LEVELS ON BOSTON NAMING TEST SCORES TO THE POPULATION IN MATARAM - Dwi Sulistyaningrum (University of Brawijaya, 2021)
Background: Obstructive Sleep Apnea (OSA) is one of the most common respiratory disorders found in society. This condition is often found in men with obesity, men with hypertension history, and elderly. In relation to this, it is found that the researches on the effect of OSA risk level on language functions is rarely done. Therefore, this study is aimed at investigating the effect of OSA risk levels on Boston Naming Test score to the population in Mataram.